Karakteristik Pendidikan Politik Kh Yusuf Hasyim dalam Mendidik para Santri - Laili Agustinaning Galuh Muninggar; Imam Sukardi; pengelola, pengelola (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2024)
Political education for students is very important so that students have a broad knowledge of politics. Santri political education starts from those closest to them, including friends, teachers or clerics. The 6th Tebuireng Islamic Boarding School caretaker is KH. Yusuf Hasyim is a person who has been involved in the national political arena. Researchers want to know the characteristics of KH's political education. Yusuf Hasyim in Educating Santri and how KH Yusuf Hasyim's contribution to politics has inspired the santri. This research is library research with a philosophical approach. Data was collected using the documentation method, namely collecting data that is relevant to the research theme with the addition of some interview data to strengthen library data. Based on the research results, it can be concluded that the characteristics of KH Yusuf Hasyim's political education are openness and freedom and when students graduate they will not only be kiai. , but there are also those who are involved in the world of politics.